Electroacupuncture Improves Clearance of Amyloid-β through the Glymphatic System in the SAMP8 Mouse Model of Alzheimer’s Disease - Pei-zhe Liang; Li Li; Ya-nan Zhang; Yan Shen; Li-li Zhang; Jie Zhou; Zhi-jie Wang; Shu Wang; Sha Yang (Neural Plasticity)
Background. Memory loss and cognitive impairment characterize the neurodegenerative disorder, Alzheimer’s disease (AD). Amyloid-β (Aβ) is the key factor that triggers the course of AD, and reducing the deposition of Aβ in the brain has been considered as a potential target for the treatment of AD. In clinical and animal studies, electroacupuncture (EA) has been shown to be an effective treatment for AD. In recent years, substantial evidence has accumulated suggesting the important role of the glymphatic system in Aβ clearance. Objective. The purpose of this study was to explore whether EA modifies the accumulation of Aβ through the glymphatic system and may thus be applied to alleviate cognitive impairments. Methods. Seven-month-old SAMP8 mice were randomized into a control group (Pc) and an electroacupuncture group (Pe). Age-matched SAMR1 mice were used as normal controls (Rc). Mice in the Pe group were stimulated on Baihui (GV20) and Yintang (GV29) for 10 min and then pricked at Shuigou (GV26) for ten times. EA treatment lasted for 8 weeks. In each week, EA would be applied once a day for the first five consecutive days and ceased at the remaining two days. After EA treatment, Morris water maze (MWM) test was used to evaluate the cognitive function; HE and Nissl staining was performed to observe the brain histomorphology; ELISA, contrast-enhanced MRI, and immunofluorescence were applied to explore the mechanisms underlying EA effects from Aβ accumulation, glymphatic system function, reactivity of astrocytes, and AQP4 polarization, respectively. Results. This EA regime could improve cognition and alleviate neuropathological damage to brain tissue. And EA treatment might reduce Aβ accumulation, enhance paravascular influx in the glymphatic system, inhibit the reactivity of astrocytes, and improve AQP4 polarity. Conclusion. EA treatment might reduce Aβ accumulation from the brain via improving clearance performance of the glymphatic system and thereby alleviating cognitive impairment.